Influence of closed incision negative-pressure therapy on abdominal donor-site morbidity in microsurgical breast reconstruction - Siegwart, Laura; Sieber, Laura; Fischer, Sebastian; Maraka, Spyridoula; Kneser, Ulrich; Kotsougiani-Fischer, Dimitra (Microsurgery, 2020)
Introduction Closed incision negative-pressure therapy (CINPT) has been shown to shorten the time to heal in post-bariatric abdominoplasty and to lower seroma rates in cosmetic abdominoplasty. The objective of this study was to assess the effect of CINPT on donor-site morbidity following abdominal-based free-flap breast reconstruction. Patients and Methods We reviewed medical records from 225 women who had undergone 300 microsurgical free-flap breast reconstructions from the abdomen from November 1, 2007 to March 31, 2019. Patients were grouped according to wound therapy, including 127 patients in the standard of care group and 98 patients in the CINPT group. Primary outcomes were minor (non-operative) and major (operative) surgical site complications. Secondary outcomes were time to drain removal, in-hospital length, and scar quality. Results Analysis of patient demographics showed an equal distribution with regard to the age, smoking status, prevalence of diabetes mellitus, preoperative chemotherapy, and previous abdominal surgery in both groups. Significantly more patients with obesity (29.6 vs. 15.8%; p = .01) and bilateral breast reconstruction (40.8 vs. 27.6%; p = .04) were included in the CINPT group. Compared to standard of care, the CINPT group had a lower incidence of major surgical site complications (26.0 vs. 11.2%; p = .001). There was no difference in minor surgical site complications and secondary outcomes between groups. Conclusion The CINPT represents a reliable tool to reduce surgical site complications on the abdominal donor-site in abdominal-based free-flap breast reconstruction.
Gesehen am 17.08.2021